TOURIST VILLAGE PORTRAIT (Case Study in Kampung Tajur, Desa Pasanggrahan, Kecamatan Bojong, Kabupaten Purwakarta) - Iyan Mugni Nugraha; Gunardi Judawinata (Institut Pariwisata dan Bisnis Internasional, 2019)
Kampung Tajur is located at the foot of Mount Burangrang Purwakarta, this area has beautiful natural scenery and cool air so that it has the potential to be used as a tourist destination. The purpose of this study is to find out the sustainability of Kampung Tajur as a tourist destination by conducting portraits wisely and based on relevant socio-economic theories. The design used is qualitative with a case study method. The results of the study show that based on the history of the chronicle and its development, Kampung Tajur has potential and has long been projected as a tourist destination. Based on their performance, Kampung Tajur tends to be categorized as a Tourism Village. Kampung Tajur is managed by the local community and the Tourism Driving Group. The Kampung Tajur management system tends to use the Top-down approach. The Kampung Tajur has several positive impacts on the economic and socio-cultural life of its people and has a negative impact, namely the decrease in the level of community harmony due to inequality in income. The sustainability of Kampung Tajur as a Tourism Village is poorly maintained due to several development efforts that tend to be less than optimal